Frequency study on panel type of FG-CNTRC joined conical-conical structures. (1st March 2021) - Talebitooti, Mostafa; Heidari Soureshjani, Ali; Pakravan, Isaac; Talebitooti, Roohollah
Highlights: The panel is modeled as two individual cones which are merged at the junctions. Thicker panels may confront with lower quantities of natural frequencies. At lower embrace angles, variations of frequencies are more than higher ones. Growth of embrace angles can reduce frequency differences of ups and downs. Shell's dynamic behavior depends strictly to semi-vertex/embrace angle of the cones. Abstract: In this paper, frequency behavior of the joined conical-conical panels is investigated while the structures are reinforced with uniform or functionally graded (FG) embedment of carbon nanotubes (CNTs). To consider both rotary inertia and in-plane effects, the formulation is developed upon FSDT considerations. By means of Hamilton's principle the dynamic equations for two cones are derived. To attach two individual panels accurately, continuity conditions is performed at the junctions to satisfy the compatibility of displacements and stress resultants. After imposing simply supported boundary conditions at the straight edges, the set of governing equations are discretized meridionally on the basis of generalized differential quadrature (GDQ) technique. The proposed discretization approach is applicable for arbitrary boundary types imposed on the two curved edges at the initiating and terminating points of the structure. The validation of results is primarily assessed via some comparisons between present data and those previous researches in the favor of individual conical panels and also finite element model for joined conical-conical type. Thereafter, the significant roles of semi-vertex angle, embrace angle, CNT parameters and boundary types on the vibrational features are discussed.